DEVELOPING POTENTIAL BASED ENTREPRENEURSHIP MODEL IN KANGEAN ISLANDS - Uswatun Hasanah; Ahmad Arsyad Munir (Journal of Management and Business, 2016)
Rural development is a spotlight during 2015 – 2019. Two issuesin the development of rural communitiesare the fact that in the past two decades, the development progress has only been focused on urban areas while in general our country the development has been dominated by rural areas and despite various efforts and rural development programsinitiated by the government in the New Order era, the socio-economic conditions of rural communities are still very far from the expected (alarming).This study aimed to develop local potential-based entrepreneurship model in Kangean islands. The development of the model becomes a model of rural settlement issues, particularly on islands. Entrepreneurship development model includes upstream downstream of local potentials capable of being expanded in agricultural and marketing sectors to become one of the tourism objects.This study used multi-methods analysisby applying LoqationQuotion (LQ) method, SWOT analysis, trend analysis, and analysis of CommunityEconomic Empowerment in agriculture and marine. The strategic value and objectiveof the study was toprovide important information on the local potentialsin Kangean islands. The results of the study indicated that the local potentials in agricultural and marine sectors could be used as tourism object. The Development model of local potential-based tourism object was intended to promotelocal potentials while maintaining the local wisdom, such as the character and local cultures.